FORMATION OF INFORMATION BASES AS THE MOST IMPORTANT STAGE OF ESTIMATION OF THE COMMERCIAL REAL ESTATE MARKET (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article substantiates the need for the formation of information bases as the first stage of the assessment of the real estate market. The tasks of information bases in the commercial real estate market are defined. An organizational scheme for the formation of information bases in the commercial real estate market has been formed and presented. Information state Internet resources are presented and characterized. The necessity of using GIS-technologies in the practice of real estate market analysis is substantiated.